Impact of administration of nicorandil prior to percutaneous coronary intervention in treatment of acute myocardial infarction: A protocol for systematic review and meta-analysis - Li, Weijun (Medicine (Baltimore), 2021)
BACKGROUND: In order to provide new evidence-based medical evidence for clinical treatment, we undertook a systematic review and meta-analysis to assess the efficacy and safety of nicorandil prior to percutaneous coronary intervention in acute myocardial infarction (AMI) patients. METHODS: This systematic review and meta-analysis will be performed according to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Two reviewers independently will search randomized controlled trials or observational studies about the treatment of nicorandil on AMI patients. Retrieved databases include Web of Science, ClinicalTrials.gov, Pubmed, Embase, and Cochrane Library. And retrieval time is limited from inception to June 2021. Key words are nicorandil, myocardial infarction, or similar expansion words without publication limitation. Biomechanical studies, in vitro studies, review articles, techniques, case reports, letters to the editor, and editorials are excluded. RESULTS: The results of our review will be reported strictly following the PRISMA criteria and the review will add to the existing literature by showing compelling evidence and improved guidance in clinic settings. OSF REGISTRATION NUMBER: 10.17605/OSF.IO/UEPKB.